MENEMBUS BATAS TRANSAKSI KONVENSIONAL: EFIKASI SOSIALISASI QRIS DALAM MENINGKATKAN DIGITAL READINESS PELAKU UMKM KELURAHAN BEBERAN V2 - Siti Fatonah; Ega Ega; Valen Valen; Zahra Zahra; Alfaridho Alfaridho; Kemal Kemal; Inggrit Inggrit; Siti Fadilah (Gapenas Publisher, 2026)
The rapid development of the digital economy ecosystem requires a fundamental transformation in the Micro, Small, and Medium Enterprises (MSMEs) sector, especially in the modernization of the payment system to strengthen business competitiveness. Beberan Village, located in Ciruas District, Serang Regency, Banten, has very strategic spatial-economic characteristics as a peri-urban transition area. Located at the intersection of the main corridor connecting Serang Regency and Tangerang Regency, adjacent to the industrial area, and supported by a heterogeneous trade sector and productive rice agribusiness, Beberan experienced rapid urbanization that shaped the character of urban society. Nevertheless, the level of digital payment literacy of local business actors is still experiencing a functional gap. This community service research aims to analyze and measure the effectiveness of the socialization of the Quick Response Code Indonesian Standard (QRIS) in increasing the digital readiness of local MSME actors. The program will be held on August 3, 2026 at the Beberan Village Office by involving 31 MSME actors in an interactive-participatory manner. The evaluation was carried out through a field experiment approach based on the before-after model (pre-test and post-test). The results of the study showed that before the socialization activity, as many as 24 out of 31 participants (77.4%) were at a superficial level of understanding qualification (just knowing) and 7 participants (22.6%) did not know QRIS at all. After being intervened through structured education, there was a massive increase in capabilities where 100% of participants achieved a comprehensive understanding of the concept, operational efficiency (fast transactions, no change), reliability of the security system (security from counterfeit money, automation of cash recording, account integration),